Risking Free Trade The Politics of Trade in Britain, Canada, Mexico, and the United States. - Lusztig, Michael (University of Pittsburgh Press, 1996)
Lusztig explores the reasons governments make the potentially dangerous decision to loosen trade restrictions. Lusztig uses examples in Britain, the United States, Canada, and Mexico to construct his own explanatory model.